Follicular and Hurthle cell carcinoma of the thyroid in iodine-sufficient area: retrospective analysis of Korean multicenter data - Kim, Won Gu (The Korean Association of Internal Medicine, 2014)
BACKGROUND/AIMS: Follicular thyroid carcinoma (FTC) and Hurthle cell carcinoma (HCC) of the thyroid are relatively uncommon thyroid malignancies in iodine-sufficient areas. In this study we evaluated the clinical behavior, prognostic factors and treatment outcomes of FTC and HCC in Korea. METHODS: This multicenter study included 483 patients with FTC and 80 patients with HCC who underwent an initial surgery between 1995 and 2006 in one of the four tertiary referral hospitals in Korea. We evaluated clinicopathological factors associated with distant metastases and recurrence during a median of 6 years of follow-up. RESULTS: HCC patients were significantly older (49 years vs. 43 years; p < 0.001) and had more lymphovascular invasions (22% vs. 14%; p = 0.03) compared with FTC patients. Distant metastases were confirmed in 40 patients (8%) in the FTC group and in two patients (3%) in the HCC group (p = 0.07). Distant metastases were significantly associated with older age, widely invasive cancer and extrathyroidal invasion. Only 14 patients (3%) had recurrent disease and there was no significant difference between FTC and HCC groups (p = 0.38). Recurrence was associated with larger tumor size and cervical lymph node metastasis. CONCLUSIONS: HCC patients were older and had more lymphovascular invasions than FTC patients. However, FTC and HCC patients had similar initial clinicopathological features. Older age, wide invasiveness and extrathyroidal invasion were independent risk factors for predicting distant metastases in FTC and HCC patients.